Open Government: Exploring Patterns of Mobile Interaction Between Citizens and Local Government. - Hilgers, Dennis; Schmidthuber, Lisa (Springer, 2018)
Public sector organizations increasingly make use of modern technology to interact with citizens. Whereas communication between citizens and public employees was characterized by one-way (e.g., front-desk) or two-way transaction (e.g., e-mail) in previous times, advances in information and communication technology provide new possibilities for citizen-government interaction such as platform-based collaboration. Leveraging innovative channels facilitates many-to-many collaboration, and enables an increased level of government openness in terms of information and citizen integration.In this exploratory study, we investigate the patterns of citizen-government interaction by focusing on an example of mobile open government. We examine which groups of citizens use the mobile application and why they are motivated to collaborate with local government. Furthermore, we analyze the interaction between mobile government users and public employees and shed light on users perception of mobile government.Survey findings provide evidence for a quite heterogeneous group of users in terms of age. However, the great majority of users are men. Users motivation for communicating with local government via mobile phone is mainly driven by their interest in forwarding concerns easily and contributing to city improvement. Regarding users activity in mobile government, results indicate that citizens with offline experience in communicating with public employees due to infrastructural defects write online reports less frequently than those without experience.This chapter contributes to a better understanding about citizens role in open government and about how individuals leverage mobile technology to collaborate with local government. To stimulate and design citizen participation more efficiently, we give some future research directions.
Keywords: Partizipation; Kommunikation; Transparenz; Kommunalverwaltung; Öffentlicher Sektor; Open Government; Bürgerbeteiligung; Digitalisierung